2018
DOI: 10.1002/micr.30304
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal reconstruction after oncological total laryngopharyngoesophagectomy: Algorithmic approach

Abstract: The proposed algorithm that ranks gastric pull-up as a priority and uses additional free tissue transfer to overcome the anastomotic tension or associated neck-skin defect is feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
(58 reference statements)
1
2
0
Order By: Relevance
“…In view of the possibility that mass tissue resection caused by tissue adhesion and necrosis of PESCC after radiotherapy failure may have a greater impact on postoperative swallowing function, we evaluated ALT and JF on swallowing function at the 6th and the 12th month postoperatively to improve the accuracy of analyzing the effects of ALT and JF on postoperative swallowing function reconstruction. Our results suggested that although the number of patients with dysphagia including liquid diet, partial tube feeding and total tube feeding in ALT and JF increased gradually with the protract of time, there was no statistical significance between the two groups, which was similar to the results of previous study [ 23 ]. However, in previous study, the results of Chan et al suggested that JF reconstruction of peripharyngectomy defects can achieve better functional outcomes than ALT, which may be different from our results, possibly because our study included patients after radiotherapy and had a small sample size [ 19 ].…”
Section: Discussionsupporting
confidence: 86%
“…In view of the possibility that mass tissue resection caused by tissue adhesion and necrosis of PESCC after radiotherapy failure may have a greater impact on postoperative swallowing function, we evaluated ALT and JF on swallowing function at the 6th and the 12th month postoperatively to improve the accuracy of analyzing the effects of ALT and JF on postoperative swallowing function reconstruction. Our results suggested that although the number of patients with dysphagia including liquid diet, partial tube feeding and total tube feeding in ALT and JF increased gradually with the protract of time, there was no statistical significance between the two groups, which was similar to the results of previous study [ 23 ]. However, in previous study, the results of Chan et al suggested that JF reconstruction of peripharyngectomy defects can achieve better functional outcomes than ALT, which may be different from our results, possibly because our study included patients after radiotherapy and had a small sample size [ 19 ].…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies have mainly focused on surgical techniques aimed at preventing early complications, such as leakage, fistula, and stricture, rather than long-term issues such as side effects of radiation therapy [ 11 , 12 , 13 , 14 , 15 ]. In contrast to these early complications, one of the most important long-term consequences in such patients is the decline in dietary function, which has a profound effect on the quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Gastric pull-up is the oldest technique still in use for reconstruction after TPLE. When introduced in 1960, the procedure was characterized by its a one-stage operation, low mortality, and the patients not being worse off than before the operation [19] . However, the limited extension of gastric tube might put the anastomosis under tension if the resection margin was too high in the oropharynx or nasopharynx.…”
Section: Introductionmentioning
confidence: 99%